Penerapan Mesin Gerinda Pengasah Pisau Dengan Sudut Ketajaman 45° Untuk Meningkatkan Proses Produksi UD. Hasil Logam - Padang Yanuar; Mochamad Denny Surindra; Ignatius Gunawan Widodo; Atikah Ayu Janitra; Sri Harmanto; Ampala Khoryanton; Slamet Priyoatmojo; Supriyo; Luqman Al Huda; Muhammad Devan Balaya (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This community service initiative was carried out to address the need to improve the productivity of the small and medium enterprises (SME) UD. Hasil Logam Kudus, which specialises in the production of animal feed chopping knives. The knife sharpening process is still carried out manually using a hand-held grinder, taking approximately 25 minutes per knife and resulting in inconsistent sharpening angles. The community engagement team from the Semarang State Polytechnic implemented grinding machine technology featuring a fixed 45° clamping system capable of sharpening three knives simultaneously. Measuring 1134 × 970 × 720 mm, the machine is powered by a 1 HP electric motor with a water-cooling system utilising a 12-volt pump. The results of the project demonstrated a 76 per cent improvement in sharpening efficiency and greater uniformity in the blade’s sharpening angle. Through the application of this appropriate technology, the partner organisation has been able to significantly increase both production capacity and product quality.